Mindfulness-Based Intervention untuk Meningkatkan Psychological Well-Being dan Spiritual Well-Being Mahasiswa - Febrianti, Thrisia; Tyas Asih, Marlia; Raharjo, Toto; Sulistyawati, Nurwinda (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
University students face various academic, social, and personal challenges that may lead to stress and a decline in well-being. This study aims to analyze the effectiveness of Mindfulness-Based Intervention (MBI) in enhancing students’ psychological well-being (PWB) and spiritual well-being (SWB), while also comparing two forms of MBI, namely meditation and journaling. This quantitative experimental study employed a repeated measures MANOVA design involving 30 students from Universitas Islam As-Syafiiyah, who were divided into three groups: MBI meditation, MBI journaling, and control. The instruments used were Ryff’s Psychological Well-Being Scale and the Spiritual Well-Being Scale developed by Paloutzian & Ellison. The findings revealed that (1) there was a significant improvement (p < 0.05) in both PWB and SWB after the intervention, which was sustained at the 4-week follow-up; (2) MBI was more effective than the control group; and (3) MBI through meditation was stronger than journaling in enhancing self-awareness, acceptance, and meaning in life. These findings highlight the novelty of comparing two variations of MBI and support the integration of MBI into counseling services to promote students’ holistic well-being.